2020
DOI: 10.2196/17914
|View full text |Cite
|
Sign up to set email alerts
|

Using Internet of Things to Reduce Office Workers’ Sedentary Behavior: Intervention Development Applying the Behavior Change Wheel and Human-Centered Design Approach

Abstract: Background Sedentary behavior (SB) is associated with various adverse health outcomes. The prevalence of prolonged sitting at work among office workers makes a case for SB interventions to target this setting and population. Everyday mundane objects with embedded microelectronics and ubiquitous computing represent a novel mode of delivering health behavior change interventions enabled by internet of things (IoTs). However, little is known about how to develop interventions involving IoT technologie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The process evaluation should be reported to provide important information about how to replicate the intervention and what generalisable knowledge can be drawn from the implementation [ 26 , 27 ]. Encouragingly, there have been several recent sit less studies published which have reported intervention development or implementation processes [ 54 , 55 , 56 , 57 ]. Finally, future research could consider contextual factors that may present as competing priorities and could consider focusing on how to alter organisational culture by challenging the social norms of workplace sitting in order to successfully implement such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The process evaluation should be reported to provide important information about how to replicate the intervention and what generalisable knowledge can be drawn from the implementation [ 26 , 27 ]. Encouragingly, there have been several recent sit less studies published which have reported intervention development or implementation processes [ 54 , 55 , 56 , 57 ]. Finally, future research could consider contextual factors that may present as competing priorities and could consider focusing on how to alter organisational culture by challenging the social norms of workplace sitting in order to successfully implement such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The WorkMyWay intervention was developed in accordance with the framework of the UK MRC for complex intervention research [26], by following through the process of identifying and summarizing the best available evidence [16], developing a theoretical understanding that is likely to account for the process of change [27], theorizing the intervention in terms of the key behavior change techniques and mechanisms, and involving the target recipients and stakeholders of the intervention throughout the development process [17].…”
Section: Interventionmentioning
confidence: 99%
“…We have previously reported, in detail, the design and development of an IoT-enabled occupational SB intervention called WorkMyWay following the Behavior Change Wheel and human-centered design approach [17]. In this paper, we report the next phase of research, namely the "feasibility phase," under the framework of the UK Medical Research Council (MRC) for developing and evaluating complex interventions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the BCW provides theory-based linkages between COM-B components, intervention functions, BCTs, and policy categories [ 27 ]. The BCW has been widely applied to design behavior change interventions that target some health-related behaviors, such as eating habits [ 31 ], sedentary behavior [ 32 ], weight management [ 33 ] and physical activity behavior [ 34 , 35 ]. Moreover, the intervention drawing on the BCW framework has showed benefits in improving the adherence to healthy eating, exercise, and body composition [ 36 ].…”
Section: Introductionmentioning
confidence: 99%